American Society for Enhanced Recovery and Perioperative Quality Initiative Joint Consensus Statement on Postoperative Gastrointestinal Dysfunction Within an Enhanced Recovery Pathway for Elective Colorectal Surgery. (June 2018) - Hedrick, Traci L.; McEvoy, Matthew D.; Mythen, Michael (Monty) G.; Bergamaschi, Roberto; Gupta, Ruchir; Holubar, Stefan D.; Senagore, Anthony J.; Gan, Tong Joo; Shaw, Andrew D.; Thacker, Julie K. M.; Miller, Timothy E.; Wischmeyer, Paul E.; et al.
Abstract : The primary driver of length of stay after bowel surgery, particularly colorectal surgery, is the time to return of gastrointestinal (GI) function. Traditionally, delayed GI recovery was thought to be a routine and unavoidable consequence of surgery, but this has been shown to be false in the modern era owing to the proliferation of enhanced recovery protocols. However, impaired GI function is still common after colorectal surgery, and the current literature is ambiguous with regard to the definition of postoperative GI dysfunction (POGD), or what is typically referred to as ileus. This persistent ambiguity has impeded the ability to ascertain the true incidence of the condition and study it properly within a research setting. Furthermore, a rational and standardized approach to prevention and treatment of POGD is needed. The second Perioperative Quality Initiative brought together a group of international experts to review the published literature and provide consensus recommendations on this important topic with the goal to (1) develop a rational definition for POGD that can serve as a framework for clinical and research efforts; (2) critically review the evidence behind current prevention strategies and provide consensus recommendations; and (3) develop rational treatment strategies that take into account the wide spectrum of impaired GI function in the postoperative period.